Cryptococcus neoformans Isolated from burn Patients in Burn Hospital in Baghdad. - Inaam K. Jassem; Sudad J. Mohammed; Tawfeq W. Tawfeq; Jassem M. Karhoot (مجلة كلية الطب, 2014)
Background: wound infections are associated with increased morbidity and mortality. Etiologic agents of wound infections vary with geographical location